CaV3.2 T-type calcium channels in peripheral sensory neurons are important for mibefradil-induced reversal of hyperalgesia and allodynia in rats with painful diabetic neuropathy. - Aleksandar Lj Obradovic; Sung Mi Hwang; Joseph Scarpa; Sung Jun Hong; Slobodan M Todorovic; Vesna Jevtovic-Todorovic (PLoS ONE, 2014)
We recently showed that streptozotocin (STZ) injections in rats lead to the development of painful peripheral diabetic neuropathy (PDN) accompanied by enhancement of CaV3.2 T-type calcium currents (T-currents) and hyperexcitability in dorsal root ganglion (DRG) neurons. Here we used the classical peripherally acting T-channel blocker mibefradil to examine the role of CaV3.2 T-channels as pharmacological targets for treatment of painful PDN. When administered intraperitoneally (i.p.), at clinically relevant doses, mibefradil effectively alleviated heat, cold and mechanical hypersensitivities in STZ-treated diabetic rats in a dose-dependent manner. We also found that CaV3.2 antisense (AS)-treated diabetic rats exhibit a significant decrease in painful PDN compared with mismatch antisense (MIS)-treated diabetic rats. Co-treatment with mibefradil (9 mg/kg i.p.) resulted in reversal of heat, cold and mechanical hypersensitivity in MIS-treated but not in AS-treated diabetic rats, suggesting that mibefradil and CaV3.2 AS share the same cellular target. Using patch-clamp recordings from acutely dissociated DRG neurons, we demonstrated that mibefradil similarly blocked T-currents in diabetic and healthy rats in a voltage-dependent manner by stabilizing inactive states of T-channels. We conclude that antihyperalgesic and antiallodynic effects of mibefradil in PDN are at least partly mediated by inhibition of CaV3.2 channels in peripheral nociceptors. Hence, peripherally acting voltage-dependent T-channel blockers could be very useful in the treatment of painful symptoms of PDN.